Susceptibility to common insecticides and detoxifying enzyme activities in Anopheles sundaicus (sensu lato) after cessation of indoor residual spraying of insecticides in the Jaffna Peninsula and its surroundings in northern Sri Lanka - Kokila, S.; Weerarathne, T.C.; Thileepan, A.; Parakrama Karunaratne, S.H.P.; Ramasamy, R.; Surendran, S.N. (Parasites & Vectors, 2019)
Abstract Background: Sri Lanka has been malaria-free since 2013 but re-introduction of malaria transmission by infected overseas travelers is possible due to a prevalence of potent malaria vectors. Knowledge of the insecticide resistance status among Anopheles vectors is important if vector control has to be reintroduced in the island. The present study investigated the insecticide susceptibility levels and resistance mechanisms of Anopheles sundaicus (sensu lato) (previously classified as Anopheles subpictus species B) an important malaria vector in the Jaffna Peninsula and it surroundings in northern Sri Lanka after indoor residual spraying of insecticides was terminated in 2013. Results: Species-specific PCR assays identified An. sundaicus (s.l.) in four locations in the Jaffna and adjacent Kilinochchi districts. Bioassays confirmed that An. sundaicus (s.l.) collected in Kilinochchi were completely susceptible to 0.05% deltamethrin and 5% malathion and resistant to 4% dichlorodiphenyltrichloroethane (DDT), whereas those from Jaffna were relatively susceptible to all three insecticides. Kilinochchi populations of An. sundaicus (s.l.) showed significantly higher glutathione S-transferase activity than population from Jaffna. However, Jaffna An. sundaicus (s.l.) had significantly higher Propoxur-resistant acetylcholinesterase activity. Activities of non-specific esterases and monooxygenases were not significantly elevated in An. sundaicus (s.l.) collected in both districts. Conclusions: The susceptibility to malathion and deltamethrin in An. sundaicus (s.l.) suggests that they can be still used for controlling this potential malaria vector in the Jaffna Peninsula and adjacent areas. Continuing country wide studies on other malaria vectors and their insecticide susceptibilities are important in this regard.
Keywords: Anopheles sundaicus complex; Jaffna Peninsula; Insecticide-detoxifying enzymes; Insecticide resistance bioassays; Malaria; Mosquito vectors; Sri Lanka